2017
DOI: 10.1098/rspb.2017.1374
|View full text |Cite
|
Sign up to set email alerts
|

Body condition explains migratory performance of a long-distance migrant

Abstract: Body condition (i.e. relative mass after correcting for structural size) affects the behaviour of migrating birds, but how body condition affects migratory performance, timing and fitness is still largely unknown. Here, we studied the effects of relative body condition on individual departure decisions, wind selectivity, flight speed and timing of migration for a long-distance migratory shorebird, the red knot Calidris canutus rufa. By using automated VHF telemetry on a continental scale, we studied knots' mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
4
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(85 citation statements)
references
References 63 publications
2
78
4
1
Order By: Relevance
“…Red knot refueling was slower in years with greater prey abundance and ruddy turnstone maintained a consistent rate of mass gain, suggesting that a slower mass gain is preferable and there may be a physiological cost of rapid refueling. Other studies have shown that individual mass predicts timing of departure from the stopover site and possibly breeding success, with heavier birds choosing more advantageous tailwinds and having a greater probability of being observed during the following autumn (Duijns et al 2017). We found no evidence for population-level delays or lack of mass gain in mismatch years, but carry-over effects from mismatches may potentially be acting on individuals to reduce survival probability or breeding success.…”
Section: Notescontrasting
confidence: 45%
See 1 more Smart Citation
“…Red knot refueling was slower in years with greater prey abundance and ruddy turnstone maintained a consistent rate of mass gain, suggesting that a slower mass gain is preferable and there may be a physiological cost of rapid refueling. Other studies have shown that individual mass predicts timing of departure from the stopover site and possibly breeding success, with heavier birds choosing more advantageous tailwinds and having a greater probability of being observed during the following autumn (Duijns et al 2017). We found no evidence for population-level delays or lack of mass gain in mismatch years, but carry-over effects from mismatches may potentially be acting on individuals to reduce survival probability or breeding success.…”
Section: Notescontrasting
confidence: 45%
“…Other studies have shown that individual mass predicts timing of departure from the stopover site and possibly breeding success, with heavier birds choosing more advantageous tailwinds and having a greater probability of being observed during the following autumn (Duijns et al. ). We found no evidence for population‐level delays or lack of mass gain in mismatch years, but carry‐over effects from mismatches may potentially be acting on individuals to reduce survival probability or breeding success.…”
Section: Discussionmentioning
confidence: 99%
“…For example, body condition is known to influence the timing of the onset of migration (Fox and Walsh , Duijns et al. ). We have observed significant differences in the body condition of tortoises both within individuals over multiple years and between individuals (Blake et al.…”
Section: Discussionmentioning
confidence: 99%
“…As energy demands are high to cross these long distances, time spent for stopover activities is higher for individuals in lower body condition [59][60][61][62][63][64][65][66][67][68][69][70][71], and hence leads to increased foraging of to allow refuelling [59,65]. Integrated over the entire migration trajectory, individuals that start migration in better body condition will therefore migrate faster, more directionally and arrive earlier at breeding sites [72][73][74][75][76]. In two anadromous fish species, migration is also negatively related to body condition, [77,78], but here this correlation is determined by local adaptation to freshwater and hence the upstream breeding grounds.…”
Section: Migrations and Stop-over Eventsmentioning
confidence: 99%